2011
DOI: 10.1371/journal.ppat.1002047
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids Trigger Cryptococcus neoformans Capsular Enlargement during Interactions with Amoebae and Macrophages

Abstract: A remarkable aspect of the interaction of Cryptococcus neoformans with mammalian hosts is a consistent increase in capsule volume. Given that many aspects of the interaction of C. neoformans with macrophages are also observed with amoebae, we hypothesized that the capsule enlargement phenomenon also had a protozoan parallel. Incubation of C. neoformans with Acanthamoeba castellanii resulted in C. neoformans capsular enlargement. The phenomenon required contact between fungal and protozoan cells but did not req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(130 citation statements)
references
References 48 publications
5
119
1
5
Order By: Relevance
“…6C). Next, a variety of small molecules were tested as candidates for the growth factor, including phosphatidylcholine, which was recently found to induce capsule formation, as well as inositol and farnesol, which act as signaling molecules in fungi (8,37,83). However, no influence on mutant growth was found (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6C). Next, a variety of small molecules were tested as candidates for the growth factor, including phosphatidylcholine, which was recently found to induce capsule formation, as well as inositol and farnesol, which act as signaling molecules in fungi (8,37,83). However, no influence on mutant growth was found (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to possible modulation of the host immune response, lipids are likely to have complex influences on C. neoformans. For example, it was recently found that phospholipids influence capsule size during cryptococcal interactions with macrophages and amoebae (8). Fatty acids or related molecules such as phospholipids and oxylipins are important signaling molecules in other fungi (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has suggested an association between Plb1 activity and titan cell formation, and this is discussed later in this review. Plb1 may be necessary to cleave certain host phospholipids to allow for activation of specific signaling pathways (39). Plb1 is secreted using the same vesicle-dependent pathway as that used by the capsule monomers.…”
Section: Attachmentmentioning
confidence: 99%
“…Investigators have speculated that this capsule may protect the fungus from environmental desiccation and/or natural predators, such as nematodes or amoebae (39,70,150,191,192,226). In the host, the capsule serves many protective functions, including reducing host immune responses by downregulating inflammatory cytokines, depleting complement components, and inhibiting the antigenpresenting capacity of monocytes (174,200,201).…”
mentioning
confidence: 99%